1998
DOI: 10.1074/jbc.273.8.4672
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor-I Receptor Internalization Regulates Signaling via the Shc/Mitogen-activated Protein Kinase Pathway, but Not the Insulin Receptor Substrate-1 Pathway

Abstract: Insulin-like growth factor-I (IGF-I) receptors activate divergent signaling pathways by phosphorylating multiple cellular proteins, including insulin receptor substrate-1 (IRS-1) and the Shc proteins. Following hormone binding, IGF-I receptors cluster into clathrincoated pits and are internalized via an endocytotic mechanism. This study investigates the relationship between IGF-I receptor internalization and signaling via IRS-1 and Shc. A mutation in the C terminus of the IGF-I receptor decreased both the rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
98
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(110 citation statements)
references
References 47 publications
11
98
1
Order By: Relevance
“…Thus, blocking endocytosis a ected only a subset of signaling functions carried out by the EGFR. Similar ®ndings were reported for the insulin like growth factor-1 receptor, an RTK of the insulin receptor family (Chow et al, 1998).…”
Section: Role Of Endocytosis In Erk Activation By Gpcrssupporting
confidence: 67%
“…Thus, blocking endocytosis a ected only a subset of signaling functions carried out by the EGFR. Similar ®ndings were reported for the insulin like growth factor-1 receptor, an RTK of the insulin receptor family (Chow et al, 1998).…”
Section: Role Of Endocytosis In Erk Activation By Gpcrssupporting
confidence: 67%
“…Previous studies 55,56 based in part on direct evidence and on homologies with the insulin receptor signaling pathways demonstrate that IGF-I binding initiates the migration of IGF-IR to clathrin-coated pits and the subsequent formation of early endosomes containing internalized but still active receptors. The ligand receptor complex ultimately becomes dissociated and inactivated in the acidic environment of late endosomes where ligands and receptors are sorted for degradation or recycling to the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…The ligand receptor complex ultimately becomes dissociated and inactivated in the acidic environment of late endosomes where ligands and receptors are sorted for degradation or recycling to the cell surface. 55,56 It has been shown that anti-IGF-IR antibodies such as MAB391 30 and scFvFc 49 induce a significant down-regulation of the IGF-IR compared to what observed when IGF-1 binds to its receptor. Our results demonstrate that both 7C10 and h7C10 are capable of inducing a degradation of the IGF-IR resulting consequently in its downregulation in both MCF-7 and A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic action of transglutaminase involves cross-linking of proteins by forming an isopeptide bond between a lysine residue of one protein and a glutamine residue of another protein during coated pit formation. MDC has been shown to block endocytosis of ␣ 2 -macroglobulin and many polypeptide hormones and cytokines like epidermal growth factor, hepatocyte growth factor, insulin-like growth factor-I, and IL-8 (37,38,40,43,44,58,60). MDC-mediated inhibition of transglutaminase has also been implicated in the blocking of endocytosis of vesicular stomatitis virus, Semliki Forest virus, and other types of endocytosis occurring through clathrincoated vesicles (61,62).…”
Section: Discussionmentioning
confidence: 99%